Beyond Security: South Korea’s Rejection Towards Us Initiative Of Trilateralism - Hasri Ainun Hakiem; Grace Lestariana Wonoadi (Ridwan Institute, 2023)
This article is a study of foreign policy that aims to understand the reasons for South Korea's refusal to join the trilateral military alliance with the U.S. and Japan in countering North Korea’s nuclear and missile provocation. Due to the crisis of the two Koreas and the North keeps doing any efforts that leads to escalate the conflict, the U.S. initiated trilateral military alliance with its allies, namely South Koarea and Japan. Surprisingly, South Korea stated that they do not want to join trilateral military alliance with U.S. and Japan.Using an extensive literature review method with an interpretive approach, it finds that South Korea’s domestic political condition and a high pressure from China regarding this issue were influential in South Korea’s decision to refuse to join the alliance. The domestic political condition refers not only to political leader, but also to historical burden, and the changing generational priorities. This study also shows that China has got a stronger bargaining position in international relations in the East Asia region.